The multifactorial complexities of autoimmune development in Pemphigus vulgaris: Critical evaluation of the role of environmental and lifestyle “exposome” factors - Adebiyi, Olumayowa T.; Galloway, Dominique F.; Augustin, Michael S.; Sinha, Animesh A. (Frontiers in Immunology, 2023)
Pemphigus vulgaris (PV) is a potentially life-threatening blistering disorder characterized by autoantibodies directed against cell-cell adhesion molecules that serves as an excellent model to study human autoimmune development. Numerous studies have identified specific Human Leukocyte Antigen (HLA) genes, in particular DRB1*0402 and DQB1*0503, that confer disease risk. Although HLA is required, it is not sufficient for the initiation of disease. As with all autoimmune diseases, the etio-pathogenesis of PV is complex, meaning it is multifactorial. Susceptibility is polygenic, and the search for non-HLA disease-linked genes continues. Moreover, twin studies across autoimmune conditions indicate that non-genetic environmental and lifestyle factors, which can be collectively grouped under the term “exposome”, are also major contributors to disease development. The literature presents evidence for the potential role of multiple triggers such as medications, infections, stress, diet, immunizations, and sleep to influence the etiology, pathophysiology, and prognosis of PV. However, a clear understanding of the degree to which specific factors impact PV is lacking. In this investigation, we comprehensively review the environmental elements listed above and consider the strength of evidence for these factors. The overall goals of this work are to provide greater insights into the factors that influence disease susceptibility, disease development and disease course and ultimately help to better guide clinicians and inform patients in the management of PV.